Review of Sarah Duffy and Michele Feist. Time, metaphor, and language: A cognitive science perspective. Cambridge University Press, 2023, 209 pp. (Language & Cognition (Cambridge University Press), 2024)
The article reviews Sarah Duffy and Michele Feist's book "Time, Metaphor, and Language: A Cognitive Science Perspective," which explores the cognitive and linguistic research on time metaphors. The book discusses how different cultures understand time metaphorically in relation to space, highlighting variations in temporal reasoning influenced by personality, culture, and linguistic factors. Duffy and Feist's work emphasizes the importance of considering individual and cultural differences in developing a comprehensive theory of metaphor's role in temporal reasoning, making it a valuable resource for scholars interested in language and cognition relationships.